PENGARUH TERAPI BERMAIN (TEKNIK BERCERITA) TERHADAP DAMPAK HOSPITALISASI PADA ANAK USIA PRA SEKOLAH DI IRINA E RSUP PROF. DR. R. D. KANDOU MANADO - Tumiwa, Finni Fitria (Coping: Community of Publishing in Nursing; Vol 9 No 1 (2021): Februari 2021DO - 10.24843/coping.2021.v09.i01.p09, 2021)
Hospitalization is a crisis situation in children, when the child is sick and must be taking care in hospital, this situation occurs because the child tries to adapt to a new and foreign environment, namely the hospital, so that this condition becomes a stressor factor for the child, both the child and the parents and their family. This study aimed to investigate the effect of the play therapy (storytelling technnique)  to the hospitalization effects on pre-school age children at IRINA E RSUP. Prof. Dr. R. D. Kandou Manado. This research uses quantitative research with one group pre-test-post-test design. The population was all pre-school age children who were treated at IRINA E RSUP. Prof. Dr. R. D. Kandou Manado. Total sampling was used to recruit 16 pre-school age children. The data obtained were then tabulated and presented in the form of a frequency distribution table, then analyzed through the T-test statistical test. The results of the analysis of this study is indicate that there is a significant relationship between play therapy and the hospitalization effects on pre-school age children who are treated at IRINA E RSUP. Prof. Dr. R. D. Kandou Manado, where the p -value = 0.000 <0.05 was obtained. In conclusion, there is a strong and positive correlation between play therapy and the hospitalization effects on pre-school age children who are treated at IRINA E RSUP. Prof. Dr. R. D. Kandou Manado. Based on the result of this study, it is suggested for nurses are expected to be able to apply simple therapies given to preschool children to reduce the impact of hospitalization.